Entry characteristics and performance in a Masters module in Tropical Medicine: a 5‐year analysis. Issue 6 (11th May 2016) - Weigel, R.; Robinson, D.; Stewart, M.; Assinder, S.
Abstract: Objectives: Postgraduate courses can contribute to better‐qualified personnel in resource‐limited settings. We aimed to identify how entry characteristics of applicants predict performance in order to provide support measures early. Methods: We describe demographic data and end‐of‐module examination marks of medical doctors who enrolled in a first semester module of two one‐year MSc programmes between 2010 and 2014. We used t‐tests and one‐wayanova to compare, and post hoc tests to locate differences of mean marks between categories of entry characteristics in univariate analysis. After exclusion of collinear variables, multiple regression examined the effect of several characteristics in multivariable analysis. Results: Eighty‐nine students (47% male) with a mean age of 32 (SD 6.4) years who received their medical degree in the UK (19%), other European (22%), African (35%) or other countries (24%) attended the 3‐months module. Their mean mark was 69.1% (SD 10.9). Medical graduates from UK universities achieved significantly higher mean marks than graduates from other countries. Students' age was significantly negatively correlated with the module mark. In multiple linear regression, place of medical degree ( β = −0.44, P < 0.001) and time since graduation ( β = −0.28, P = 0.007) were strongest predictors of performance, explaining 32% of the variation of mean marks. Conclusion: Students' performance substantially differs based on their entry criteria in this 1st semester module. Non‐UK graduates and mature students might benefit from early support.